Differential diagnosis of bladder versus colorectal adenocarcinoma: keratin 7 and GATA3 positivity in nuclear ß-catenin-negative glandular tumours defines adenocarcinoma of the bladder. Issue 4 (13th October 2015) - Broede, Anna; Oll, Matthias; Maurer, Angela; Siegert, Sabine; Stoerkel, Stephan; Golz, Reinhard; Schwamborn, Kristina; Veeck, Jürgen; Knuechel, Ruth; Gaisa, Nadine T
Abstract : Aims: This study evaluates immunohistochemical markers for the differential diagnosis of primary bladder adenocarcinoma (BAC) from secondarily involving colorectal adenocarcinoma (CAC). Additional staining of putative precursor lesions (cystitis cystica et glandularis (CC) and intestinal metaplasia (IM)) supports insights into metaplastic cell development and aberrant differentiation in tumours. Methods: Tissue microarray sections of formalin-fixed, paraffin-embedded tissues from clinically verified 11 BAC, 11 CAC, 18 invasive urothelial carcinomas (UCs), 22 normal urothelium samples, 25 CC and 15 IM were stained for keratin 7, 5/6, 5/14 and 20, ß-catenin, e-cadherin, cadherin 17, cdx2, uroplakin II and III, CD10, androgen receptor (AR), S100P, MUC2, MUC5AC and GATA3 expression. Data were analysed using Kruskal–Wallis/Dunn's multiple comparison test and Fisher's exact test. Results: Significant difference (p<0.05) between all three tumour groups was observed for keratin 7 only. Further significant difference between BAC and CAC was found for GATA3 and nuclear ß-catenin staining. BAC-positive/CAC-negative markers without significance were: p63, keratin 5/6, 5/14, uroplakins II/III and AR. CC showed a urothelial phenotype (p63+, GATA3+, S100P+, uroplakin+ in single cells) with initial signs of intestinal differentiation (single cells cdx2+ or cadherin 17+). IM displayed a full intestinal phenotype (p63−, all urothelial markers-, cdx2/MUC2/MUC5AC+, cadherin17+). Conclusions: Differential diagnosis of BAC and CAC remains difficult, but positive staining for keratin 7 in nuclear ß-catenin-negative tumours argues for BAC. Additional markers like GATA3 and p63 may be added, as positivity in some cases may be helpful. However, for reliable histological diagnosis, knowledge of comprehensive clinical data is still essential.